2021
DOI: 10.1038/s41598-021-95689-x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen–Albumin-Ratio is an independent predictor of thromboembolic complications in patients undergoing VA-ECMO

Abstract: Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) supports patients suffering from refractory cardiogenic shock. Thromboembolic complications (TeC) are common in VA-ECMO patients and are associated with increased morbidity and mortality. Valid markers to predict TeC in VA-ECMO patients are lacking. The present study investigated the predictive value of baseline Fibrinogen–Albumin-Ratio (FAR) for in-hospital TeC in patients undergoing VA-ECMO. This retrospective cohort study included patients who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Finally, a high fibrinogen level (≥ 6 g/L) was associated with greater odds of thrombosis. Elevated fibrinogen levels have been associated with thrombosis risk in the general population [59,60] but the evidence in ECMO patients remains scarce [61].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a high fibrinogen level (≥ 6 g/L) was associated with greater odds of thrombosis. Elevated fibrinogen levels have been associated with thrombosis risk in the general population [59,60] but the evidence in ECMO patients remains scarce [61].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the high clinical usefulness of the FAR assessment was also demonstrated in the study by Roth et al, which included 344 patients with cardiogenic shock refractory who underwent veno-arterial extracorporeal membrane oxygenation (VA-ECMO). It was shown that a higher FAR was significantly associated with the risk of in-hospital thromboembolic complications (OR = 3.72; 95% CI: 2.26–6.14) [ 56 ]. The FAR assessment may also be useful in assessing the severity of CAD.…”
Section: Fibrinogen and Cardiovascular Riskmentioning
confidence: 99%
“…13,14,22 Emerging publications showed that AFR is, in fact, superior to albumin in reflecting nutritional status, and in predicting postoperative patient prognosis. 15,23 For instance, a recent study by Fang et al demonstrated that AFR possesses strong prognostic capability, and accurately predicts the overall survival of patients with pancreatic cancer. 13 Likewise, Seoyeong and colleagues reported that the preoperative FAR is a prognostic biomarker for mortality after off-pump coronary artery bypass grafting, and an elevated FAR (reduced AFR) value is intricately linked to an enhanced postoperative all-cause mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…Being a readily measured biomarker of nutritional status, AFR was previously proposed to correlate with the clinical outcomes of a variety of human diseases 13,14,22 . Emerging publications showed that AFR is, in fact, superior to albumin in reflecting nutritional status, and in predicting postoperative patient prognosis 15,23 . For instance, a recent study by Fang et al demonstrated that AFR possesses strong prognostic capability, and accurately predicts the overall survival of patients with pancreatic cancer 13 .…”
Section: Discussionmentioning
confidence: 99%